Drying of mango slices using a cabinet dryer retrofitted with ricehull-fired furnace - Daquila, Robelyn E. (Philippine agricultural mechanization journal)
The project was undertaken to develop a cabinet dryer retrofitted with rice hull furnace and determine its performance in drying mango slices. The cabinet dryer had a capacity of 240 kg/batch, three racks which accommodated 50 drying trays, and kerosene burner with heat exchange. Mango slices with initial moisture content of 50.7 percent were dried in nine and half hours (9.5 h) uniformly down to 11.6 percent final moisture content. The developed furnace had automatic husk feeding and ash unloading mechanisms, temperature controller, heat exchanger and fly ash scrubber. Performance tests showed that at rice hull consumption rate of 13.8 to 14.5 kg/h, the furnace attained efficiencies of 52.2 to 54.8 which were above the 50 percent minimum acceptable level set by PAES. The rice hull furnace was successfully retrofitted to the cabinet dryer. Cost analysis showed that total drying cost was reduced from Php 25.98/kg to Php 19.29/kg of dried mango when the kerosene burner was replaced with rice hull furnace. Quality analysis of dried mango slices from the retrofitted cabinet dryer showed no significant reduction in B-carotene content of dried products. Also, microbial load analysis indicated the dried products passed the standard for maximum allowable microbial load. Lastly, sensory evaluation showed that dried mango slices from retrofitted cabinet dryer was comparable with current commercial products from the mango processor.